DESIGN, SYNTHESIS AND INTERPRETATION OF FLUORESCENT HEMODOSIMETER BASED ON DENSITY FUNCTIONAL THEORY - Quý Phan Tứ; Quang Dương Tuấn; Tùng Trương Quý (Hue University Journal of Science: Natural Science, 2017)
This work presents the design and synthesis theories of chemodosimeter FS to determine Hg2+ based on lactam ring-opening reaction of fluorescein derivative using density-functional theory (DFT). All theoretical calculations including DFT, TD–DFT, and NBO were carried out with the B3LYP function Gaussian03 software. The comparison of geometric parameters (bond lengths, bond angle, and dihedral angles of atoms) of fluorescein optimized with two basis sets LanL2DZ and 6-311+G(d, p) by means of t–test pairs suggested that LanL2DZ not only reduced the computation time but also gave reliable results. Fluorescent properties of the chemodosimeter FS were explained through TD–DFT and NBO analysis. The results showed that FS was non-fluorescent because of π conjugated system interruption which was due to the existence of the lactam ring. In FG, a product of the reaction between FS and Hg2+, the lactam ring structure was disrupted, and 1,3,4-oxadiazole was formed, resulting in the existence of a conjugated π system from the fluorophore to the receptor, and therefore FG was fluorescent. Accordingly, FS is predicted as an OFF–ON chemodosimeter.